Association of epicardial adipose tissue with coronary CT angiography plaque parameters on cardiovascular outcome in patients with and without diabetes mellitus. (December 2022) - Tesche, Christian; Bauer, Maximilian J.; Straube, Florian; Rogowski, Sebastian; Baumann, Stefan; Renker, Matthias; Fink, Nicola; Schoepf, U. Joseph; Hoffmann, Ellen; Ebersberger, Ullrich
Abstract: Background and aims: We aimed to evaluate the association of epicardial adipose tissue (EAT) with coronary CT angiography (CCTA) plaque parameters on cardiovascular outcome in patients with and without diabetes mellitus. Methods: Data of 353 patients (62.9 ± 10.4 years, 62% male), who underwent CCTA as part of their clinical workup for the evaluation of suspected or known CAD, were retrospectively analyzed. EAT volume and plaque parameters from CCTA were compared in patients with diabetes ( n  = 63) and without diabetes ( n  = 290). Follow-up was performed to record adverse cardiovascular events. The predictive value to detect adverse cardiovascular events was assessed using concordance indices (CIs) and multivariable Cox proportional hazards analysis. Results: In total, 33 events occurred after a median follow-up of 5.1 years. In patients with diabetes, EAT volume and plaque parameters were significantly higher than in patients without diabetes (all p  < 0.05). A multivariable model demonstrated an incrementally improved C-index of 0.84 (95%CI 0.80–0.88) over the Framingham risk score and single measures alone. In multivariable Cox regression analysis EAT volume (Hazard ratio[HR] 1.21, p  = 0.022), obstructive CAD (HR 1.18, p  = 0.042), and ≥2 high-risk plaque features (HR 2.13, p  = 0.031) were associated with events in patients with diabetes and obstructive CAD (HR 1.88, p  = 0.017), and Agatston calcium score (HR 1.009, p  = 0.039) in patients without diabetes. Conclusions: EAT, as a biomarker of inflammation, and plaque parameters, as an extent of atherosclerotic CAD, are higher in patients with diabetes and are associated with increased adverse cardiovascular outcomes. These parameters may help identify patients at high risk with need for more aggressive therapeutic and preventive care. Graphical abstract: Image 1 Highlights: CT-derived EAT volume and plaque parameters were significantly higher in patients with diabetes than without. EAT volume and plaque parameters demonstrate high predictive value for adverse cardiovascular outcome. A multivariable model with EAT volume and plaque parameter demonstrated improved C-index over FRS and single measures alone.